2019
DOI: 10.1111/sltb.12550
|View full text |Cite
|
Sign up to set email alerts
|

Kognito's Avatar‐Based Suicide Prevention Training for College Students: Results of a Randomized Controlled Trial and a Naturalistic Evaluation

Abstract: Objective To evaluate the efficacy and effectiveness of Kognito At Risk for College Students, an online, interactive suicide prevention gatekeeper training. Methods In Study 1, a randomized controlled trial was conducted to test the efficacy of Kognito. Retention of participants at follow‐up was strong. In Study 2, administrative records were used to follow the help‐seeking behavior of Kognito trainees for one academic year, contrasted with untrained students. Results In Study 1, between‐group changes in gatek… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…In an RCT evaluating Kognito's effectiveness for students, it was found that self-reported prevention behaviours improved following training, with the likelihood of seeking help for themselves also improving, but this was not sustained at follow-up. An examination of archival records also showed that students who had completed the training had greater help-seeking behaviours/practices than those who had not completed the training [33].…”
Section: Gatekeeper Training Programsmentioning
confidence: 99%
See 2 more Smart Citations
“…In an RCT evaluating Kognito's effectiveness for students, it was found that self-reported prevention behaviours improved following training, with the likelihood of seeking help for themselves also improving, but this was not sustained at follow-up. An examination of archival records also showed that students who had completed the training had greater help-seeking behaviours/practices than those who had not completed the training [33].…”
Section: Gatekeeper Training Programsmentioning
confidence: 99%
“…Two studies evaluated the effectiveness of 'Kognito' which was the sole online gatekeeper training program. Kognito uses avatar-based training involving realistic virtual scenarios to train staff and students on identifying individuals at risk, selecting interventions and talking about suicide [21,33]. This training program seeks to prepare individuals to support students at risk, but also to improve participants' own help-seeking attitudes and behaviours [33].…”
Section: Gatekeeper Training Programsmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies have found that virtual role play practices can provide an efficacious means of delivering screening and brief intervention training for health care providers [29][30][31][32][33][34], and have proven to successfully change attitudinal constructs and behaviors in K12 and higher education settings related to identifying; talking to; and, if necessary, referring students in psychological distress. [29,[35][36][37][38][39]. Virtual role play simulations that integrated MI techniques were equally effective across multiple races and ethnicities including people who were Black, Hispanic, Latinx, White, Asian, and American Indian or Alaska Native [40,41].…”
Section: Simulation Platform and Efficacy Researchmentioning
confidence: 99%
“…Avatar‐based interventions refer to a computer‐simulated interaction where the user has some level of control over a character in the simulation. Avatar‐based interventions offer the following benefits compared with in‐person interactions (e.g., role play, standardized patient interaction): Accessible to more people, adherence to the intervention protocol, controlled alteration of scenarios, ability to collect participants’ data, and access not bound by time or location (Albright et al, 2012; Coleman, Black, Ng, & Blumenthal, ; Hayes‐Roth et al, ). Avatar‐based interventions can provide constant and immediate feedback, which triggers in‐depth thinking, helps with learning from mistakes, and enhances engagement in the intervention (Albright et al, 2012; Cate & Albright, ; Wilson, ).…”
Section: Introductionmentioning
confidence: 99%